2011
DOI: 10.4103/0253-7176.85392
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Social Support

Abstract: Background:This is an experimental study and it discusses the effectiveness of social support in managing academic stress among students.Aim:The purpose of this study is to understand the importance of social support in managing stress.Materials and Methods:Simple random sampling was assigned to a number of 120 students, equally divided into an experimental and a control group. Classes on social support as coping mechanisms were given to the experimental group only. The accumulated data were then analyzed, des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 14 publications
3
42
0
7
Order By: Relevance
“…A versatile private life including sport and social support showed no significant connection to stress or depressive symptoms in our study. Even though social support has proven to be a strong coping strategy to deal with stress and burden in several studies, Baqutayan [28] showed that only social support based on counseling lessons had a significant positive effect on stress in young students. Support from friends and family showed no significant effects.…”
Section: Discussionmentioning
confidence: 99%
“…A versatile private life including sport and social support showed no significant connection to stress or depressive symptoms in our study. Even though social support has proven to be a strong coping strategy to deal with stress and burden in several studies, Baqutayan [28] showed that only social support based on counseling lessons had a significant positive effect on stress in young students. Support from friends and family showed no significant effects.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Daugherty and Lane (1999) found that establishing social bonds and friendship support networks with college peers and academic advisors during the first-year transition improved academic performance and psychological wellbeing. Having a high perception of availability for social support friends and family have also been found to alleviate homesickness (Baqutayan, 2011) We believe that social support, especially within the collective society of China, might play an vital part in alleviating symptoms of stress particularly uprooting stress. Unfortunately, we did not examine the role of social support in dealing with uprooting stress, but it should be considered in future research.…”
Section: Discussionmentioning
confidence: 89%
“…This finding suggests that participants with less perceived family social support tended to have high perceived stress scores. In general, social support helps individuals cope during stressful situations (Baqutayan, 2011;Mills, Reiss, & Dombeck, 2008). The sample in this study may have used their family social support to handle stress.…”
Section: Research Questionsmentioning
confidence: 99%